Agenda Setting and Political Control in India's Sanitation Policy Subsystem. (September 2017) - Martel, J.C.
India has the worst sanitation situation in the world. Over the past century, Indian political leaders have made public statements expressing the intensity of the problem, deeming sanitation more important than political freedom, independence and religion. Recently, two prominent political parties—National Congress and Bharatiya Janata—argued about who deserves credit for improving India's cleanliness. In response, this article is guided by the question: Does it matter which political institutions are supporting sanitation improvements in India? Using two theoretical lenses, agenda setting and political control of bureaucracy, this article discusses (1) the problem, politics and policies in India's sanitation policy subsystem, and (2) mechanisms to align policy preferences across levels of government. Utilizing an agenda setting conceptual framework, the discussion highlights the role of international organizations in problem identification; party ideology and values and capacity issues that challenge the policy arena. The discussion turns to alignment of policy preferences across India's multi-level governance structure, pointing to monitoring to reduce principal-agent problems, drawing from political control of bureaucracy theory. Given that national political leaders observably support sanitation, this article proposes that aligning policy preferences between national political institutions and local implementation agencies is imperative for achieving sanitation policy goals in federalist India.